Between neo-liberalism and the nation: France's political landscape in 2022. (2nd October 2022) - Chabal, Emile; Behrent, Michael C.
ABSTRACT: France's 2022 electoral cycle suggests that the basic contours of French politics are in flux. This is largely because the traditional left-right spectrum proved increasingly incapable of structuring France's political supply through the 1990s and 2000s. The result has been a reconfiguration of the political spectrum along a new quadripolar axis, in which political actors and voters position themselves along two spectrums: neoliberal-anti-neoliberal and globalist-nationalist. This quadripolar system has changed the way French parties operate and the way political actors present themselves. It has also given rise to—and reinforced—emerging patterns of electoral sociology and geography, which became particularly evident after the 2022 legislative elections.